Dynamics and control of ochratoxigenic strains of Penicillium Verrucosum and Aspergillus Ochraceus in the stored grain ecosystem - Cairns-Fuller, Victoria (Cranfield University, 2004)
This study investigated the effect of interacting environmental factors on the ecophysiology of Penicillium verrucosum and Aspergillus ochraceus and ochratoxin A (OTA) production and potential for controlling growth and OTA production using essential oils and resveratrol on wheat grain. Two dimensional temporal profiles of growth and OTA production were constructed for the first time and showed that the water activity (aw) ranges required for growth and OTA production were different in vitro and on wheat grain. Growth occurred over a wider aw range than OTA production for P. verrucosum and A. ochraceus respectively regardless of the temperature tested. For example, P. verrucosum grew at 0.80-0.995 aw on wheat grain however OTA production occurred between 0.85-0.995 aw. A. ochraceus grew at 0.80-0.995 aw on wheat grain however OTA production occurred between 0.85-0.995 aw. Optimum OTA production was at intermediate aw ranges (0.93-0.98 aw) and increased with incubation period. Interestingly at sub-optimal aw there was a' stimulation in OTA production by A. ochraceus at 15-25 oC on wheat grain. Cont/d..